Impact of physical activity on quality of life in the elderly - Kusumaratna, Rina K. (Universa Medicina, 2008)
The rapid growth of the elderly population is having an impact on the maintenance of a healthy mental and physical state. The aim of this study was to assess the correlation of physical activity and quality of life in the elderly. The participants in this study were 21 male and 80 female elderly persons (66.4 Â± 6.3 years, mean Â± SD) recruited from the community in 2 subdistricts in South Jakarta. Data were collected on the quality of life (QOL) using the WHOQOL-BREF questionnaire that contains 26 items, 24 of them making up the 4 domains of physical health, psychological health, social relationships, and environment. The Short Form (SF) International Physical Activity Questionnaire (IPAQ) was used to measure the habitual practice of physical activities of the elderly. Subjects were separated into groups with low (n = 25), moderate (n= 37) and high activity level (n = 39), according to their position on the physical activity scale. The QOL scores in all four domains were significantly higher (p < 0.05) in the group reporting a higher level of physical activity. After adjustment for age, the more active group had higher values in all four QOL domains as follows: physical health (p = 0.027), psychological health (p = 0.000), social relationships (p = 0.005), and environment (p = 0.000). Healthy older adults who had higher physical activity had higher QOL scores than those who were physically less active. Therefore, incorporating more physical activity into the lifestyles of sedentary or minimally active elderly persons may improve their QOL.